Quantitative decision making with spreadsheet application - Lapin, Lawrence L. (Thomson, 2001)
Quantitative decision making with spreadsheet application has been to provide a complete and modern treatment of basic management science methodology. The book is written for college students who have only a limited algebra background. Even more important, it is designed to provide them with a feeling for the variety and power of management science tools, to alleviate their apprehension of the subject, and to enable them to recognize on-the-job sutuations in which management science methodology can be successfully employed